Non‐coding RNAs in bone remodelling and bone metastasis: Mechanisms of action and translational relevance. (11th December 2019) - Puppo, Margherita; Taipaleenmäki, Hanna; Hesse, Eric; Clézardin, Philippe
Abstract : Bone metastases are frequent complications in patients with advanced cancer, which can be fatal or may rapidly impede the quality of life of patients. Current treatments for patients with bone metastases are palliative. Therefore, a better understanding of the molecular mechanisms that precede the overt development of skeletal lesions could lead to better therapeutic interventions. In this review, we present evidence that non‐coding RNAs (ncRNAs) such as long ncRNAs, microRNAs, and circular RNAs are emerging as master regulators of bone metastasis formation. We highlight potential opportunities for the therapeutic targeting of ncRNAs. Furthermore, we discuss the possibility that ncRNAs may be used as biomarkers in the context of bone metastases, which might provide insight for improving the response to current bone‐targeting therapies. LINKED ARTICLES: This article is part of a themed issue on The molecular pharmacology of bone and cancer‐related bone diseases. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v178.9/issuetoc